Substituent Effects on the Activation Parameter Changes for the Aminolysis in the Bimolecular Nucleophilic Reactions in Solution - Vlasov, Vladislav M. (Journal of Applied Solution Chemistry and Modeling, 2014)
Variation of the activation parameters for the aminolysis in the SN2, acyl-transfer, SNAr and AdN reactions offers an additive mechanistic tool for the studies of these reactions in solution. This approach uses the substituent effects on the benzene and pyridine rings to the variation of the activation parameters, ΔX≠ (X = H, S, G), in the above reactions in the frameworks of the Hammett - like equations in order to evaluate the resultant δΔX≠ reaction constants. The single linear dependences of the internal enthalpy constants δΔH≠ int on the δΔG≠ and the Hammett Ï constants show that the substituent effects in the leaving and nonleaving groups and nucleophiles on the mechanistic features in aminolysis of bimolecular nucleophilic reactions are governed by the magnitude of δΔH≠ int when one of the steps of the process is the single rate-determining step.